Peran Mediasi Kepercayaan Pada Pengaruh Kualitas Website Dan E-Wom Terhadap Minat Beli Ulang Di Tokopedia Oleh Konsumen Online Generasi Milenial Di Daerah Istimewa Yogyakarta - Maria Dwisakti Nettilin Watu; Haddy Suprapto; Dyah Sugandini (Jurusan Teknik Informatika, 2021)
This study aims to analyze the mediating role of trust on the influence of website quality and E-WOM on the repurchase intention at Tokopedia by online consumers of millennial generation in D.I. Yogyakarta. This type of research is quantitative research. The sample in this study is part of the online consumers of millennial generation in D.I. Yogyakarta who have made a purchase at Tokopedia in the last 6 months with a minimum of twice purchases on Tokopedia. The sampling technique used purposive sampling, the data collection method in this study used a questionnaire. Questionnaires were distributed online using google form to 100 respondents. The data analysis technique in this study uses Partial Least Square (PLS) with the SmartPLS 3.3.3 software application. The results show that 1) website quality has a direct effect on repurchase intention, 2) E-WOM has a direct effect on repurchase intention, 3) website quality affects repurchase interest with trust as a mediating variable and 4) E-WOM has an effect on repurchase interest with trust as a mediating variable.